2021
DOI: 10.1371/journal.pone.0260442
|View full text |Cite
|
Sign up to set email alerts
|

Plasma obtained following murine hindlimb ischemic conditioning protects against oxidative stress in zebrafish models through activation of nrf2a and downregulation of duox

Abstract: Ischemia/reperfusion of organ systems in trauma patients with resuscitated hemorrhagic shock (HSR) contributes to tissue injury and organ dysfunction. Previous studies using a murine model of HSR showed that remote ischemic preconditioning (RIC) protected against organ injury and that the plasma was able to prevent neutrophil migration in a zebrafish tailfin-cut inflammation model. In this study, we hypothesized that RIC plasma inhibits neutrophil function through a decrease in reactive oxygen species (ROS) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Remarkably, the AT group presented the lower number of both, macrophages and neutrophils, in the injured tissue. Thus, a decrease in macrophage activation, neutrophil trafficking, adhesion capacity and chemotaxis was observed, with proteins down-regulated (ALOX5AP, CD14, CORO1A, CTSB, FCER1G, IL1RN, LBP) [ 98 105 ] and up-regulated (NQO1, PROCR, TIPE2) in AT and CB mice compared to IC ones, as it was also previously reported [ 106 108 ]. Overall, our results indicated that the combination of AT-MSC with either AT- or CB-ECFCs alleviated the impact of the negative effects of ischemia, reducing inflammation but also tissue necrosis.…”
Section: Discussionsupporting
confidence: 71%
“…Remarkably, the AT group presented the lower number of both, macrophages and neutrophils, in the injured tissue. Thus, a decrease in macrophage activation, neutrophil trafficking, adhesion capacity and chemotaxis was observed, with proteins down-regulated (ALOX5AP, CD14, CORO1A, CTSB, FCER1G, IL1RN, LBP) [ 98 105 ] and up-regulated (NQO1, PROCR, TIPE2) in AT and CB mice compared to IC ones, as it was also previously reported [ 106 108 ]. Overall, our results indicated that the combination of AT-MSC with either AT- or CB-ECFCs alleviated the impact of the negative effects of ischemia, reducing inflammation but also tissue necrosis.…”
Section: Discussionsupporting
confidence: 71%
“…In transient limb ischemia, remote ischemic conditioning confers neuroprotection in part by countering injury-induced ROS generation in a Nrf2-dependent fashion ( 120 , 121 ). In animals with ICH, remote ischemic conditioning can attenuate brain edema by upregulating heme oxygenase-1, transferrin, and transferrin receptor ( 122 ), and promoting hematoma resolution via increasing anti-inflammatory macrophage activation ( 123 ).…”
Section: Treatment Of Ich With Anti-os Agentsmentioning
confidence: 99%